Time an effectiveness (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
Current lifestyle promotes instantaneity and hastiness. This is especially true for journalism, since it is linked to news and present because of its nature, but too often urgency is detrimental to both analysis and reflexivity. Dedicated to cultura, literatura and arts, cultural journalism appears as a refuge for freedom of thought and expression, and seems to be less subdued to haste. However, cultural industry is usually more powerful tan cultura itself, and commercial interests prevail over quality. This paper analyzes this situation and upholds values such as reflection, well prepared work and elitism as an antidote to mercantilism and triviality in cultural journalism.
Keywords: cultural journalism; critical journalism; literary criticism